IMPLEMENTASI METODE JUST IN TIME DALAM PENGENDALIAN BAHAN BAKU PT. ALLIANCE CONSUMER PRODUCTS INDONESIA (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
ABSTACT Soap noodle is the main raw material in PT. Alliance Consumer Products Indonesia where the raw material control applied uses traditional methods were affected to the inefficiency of process and production cost. The purpose of this inventory control research is specifically to reduce the cost of raw material inventory. Lack of or too much inventory of raw materials has a bad impact on a sustainable production process on the other hand affects the cost of storing and maintaining raw material inventory. Research on controlling soap noodle raw materials at PT. Alliance Consumer Products Indonesia uses just in time calculations. just in time method as an alternative in controlling raw material inventory is chosen based on the relevance of the company in order to improve the efficiency of raw material inventory control and minimize inventory costs. The results of the calculation of the need for raw material for soap noodles using the just-in-time method are 107.760 tons per year with an optimal number of orders of 1.959.74 tons. To meet the needs of raw materials with an optimal number of orders 54.99 times (55 times rounding) in one year with a quantity per order of 1,959.74 Tons. The frequency of delivery per order is 4 times with a total of 489.94Ton per shipment. By using the just in time method, it can be concluded that the total cost of finished raw material inventory is Rp. 16,334,753.91 while the company's policy is Rp. 31,920,000. When compared with cost efficiency, the savings are Rp. 15,585,246.09. Keywords: Inventory Control, Raw Material, Just in Time.